Active gaming in Dutch adolescents: a descriptive study - Simons Monique; Bernaards Claire; Slinger Jantine (BMC, 2012)
Abstract Background Adequate levels of physical activity are part of a healthy lifestyle and in this way linked to better health outcomes. For children and adolescents, the physical activity guideline recommends at least 60 minutes of moderate-to-vigorous physical activity every day. However, many adolescents are not physically active enough and they spend a lot of their time on sedentary activities (such as video games). A new generation of video games that require body movements to play them, so-called "active games", could serve to increase physical activity in adolescents. The activity level while playing these games is comparable to light-to-moderate intensity physical activity. The current study aims to increase our understanding of 1) the demographic characteristics of adolescents who play active games regularly (≥ 1 hour per week) and non-regularly (<; 1 hour per week), 2) time spent on active games, 3) the contribution of active games to daily physical activity and 4) the type and amount of activities being replaced by active gaming. Methods A cross-sectional survey was conducted in a Dutch internet panel, questioning adolescents in conjunction with one of their parents. A random sample of 320 households (with stratification on gender of the parent and the adolescent, the age of the adolescent and the region of the household) was selected that owned a console or application for active video games and that had a child aged 12 through 16 years. 201 child-parent couples (63% response) completed an internet survey with questions about demographics, physical activity and sedentary behaviour, and gaming behaviour. The questionnaire also contained questions designed to assess whether and how active gaming replaces other activities. Besides descriptive analyses, independent t-test, Pearson's chi-square and Mann-Whitney test (when data were not normally distributed) were used for comparisons between regular and non-regular active gamers. Results Eleven percent of the adolescents with an active game in their household never used the game. There were no significant differences in gender, education level (of adolescent and parent), ethnicity and sedentary behaviour between regular (n = 65) and non-regular active gamers (n = 114). Adolescents' (regular and non-regular active gamers) meantime spent on active gaming was 80 (± 136) minutes a week; this potentially amounts to 11% of total physical activity. When time spent on active gaming was included in the calculation of the percentage of adolescents that met the physical activity guideline, the percentage increased significantly (p <; 0.05) from 67 to 73%. According to the adolescents, active gaming mainly replaces sedentary screen time such as TV viewing, internet and non-active gaming. Parental opinions concurred with this appraisal. Conclusions The results of this study confirm the idea that active gaming may contribute to an active lifestyle in adolescents, primarily because it potentially contributes substantially to time spent on physical activity. Secondly, active gamers indicate that they spent time on active games which they would have spent otherwise on less active activities.